Social innovation activities in Japanese firms: A pilot study with text mining - Zhao, W. L.; Ouchi, N.; Watanabe, C. (2016 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM), 2016)
Nowadays, people are aware that many of the social changes and problems facing humanity cannot be solved by economic development or technological change alone. In recent years, many researchers have called for more attention to be given to social demand and social change. Although the concept of social innovation is still vague, solving social challenges through social innovation is considered to be important. At the same time, researches have been conducted on the importance of social enterprises and social entrepreneurs as players in social innovation. In addition to these researches, the roles and activities of firms in promoting social innovation should be focused on. This paper explores Japanese firms' social innovation activities by analyzing newspaper articles. The results show that firms tend to undertake social innovation by connecting their regular or core businesses with social innovation activities rather than building an innovative way to create social innovation.
ISSN: 2157-362X
Keywords: Asie; Réservé UdeM